Migration and Citizenship Legal Status, Rights and Political Participation - Bauböck, Rainer (IMISCoe Reports, 2006)
Citizenship is frequently invoked both as an instrument and goal of immigrant integration. Yet, in migration contexts, citizenship also marks a distinction between members and outsiders based on their different relations to particular states. A migration perspective highlights the boundaries of citizenship and political control over entry and exit as well as the fact that foreign residents remain in most countries deprived of core rights of political participation. This book summarizes current theories and empirical research on the legal status and political participation of migrants in European democracies.